Evaluating the Mechanical Properties of Nanocomposites in Restorative Dentistry: A Comparative Study of Strength, Durability, and Aesthetic Performance - Ikram, Amna Mehwish; Mohamad, Dasmawati; Shahzad, Aamir; Kausar, Rehana; Iqbal, Ayousha; Saba, Kiran (Journal of Neonatal Surgery, 2025)
Background: The advancement of restorative dental materials has emphasized achieving an ideal balance between mechanical durability and aesthetic excellence. This study aimed to compare the mechanical and aesthetic performance of three contemporary resin-based restorative materials nanoceramic, nanohybrid, and nanofilled composites, before and after simulated aging. Methods: A total of 90 specimens were fabricated and equally divided among the three material groups. Mechanical properties, including flexural strength, fracture toughness, surface hardness, and wear resistance, were evaluated following standardized protocols. Aesthetic parameters such as color stability (ΔE), surface roughness, and gloss retention were assessed before and after immersion in coffee and tea solutions for seven days to simulate staining. Data were analyzed using ANOVA and Pearson correlation tests, with a significance level of p ≤ 0.05. Results: Nanoceramic composites demonstrated significantly higher flexural strength (152.4 ± 9.6 MPa) and fracture toughness (2.17 ± 0.18 MPa·m½) compared to nanohybrid and nanofilled materials (p < 0.001). Strong negative correlations were observed between flexural strength and color change (r = -0.62, p < 0.001) and between wear resistance and surface roughness (r = -0.65, p < 0.001). Conclusion: Nanoceramic composites offer the best combination of strength, wear resistance, and aesthetic stability among the tested materials. Their improved filler technology ensures superior long-term performance, making them the material of choice for restorations requiring both durability and high aesthetic standards.